Zapalenie nerwu wzrokowego i siatkówki w przebiegu choroby kociego pazura - Karolak, Joanna; Gotz-Więckowska, Anna (Klinika Oczna / Acta Ophthalmologica Polonica, 2010)
Purpose: To present two cases of neuroretinitis in cat scratch disease. We present two girls treated in Department of Ophthalmology of Poznań University of Medical Sciences because of unilateral, painless decrease of vision. Both patients presented following cat exposure fever and lymph nodes swelling. Ophthalmoscopic findings was neuroretinitis (optic disc edema with the macular star). Bartonella henselae antibody titers (IgG) were elevated. CSD is usually self-limited infection in immunocompetent patients and there is no clear treatment recommendations. One of our patients received treatment which included oral antibiotic (macrolides) and steroid. The second patient was left without treatment. In our case – the duration of visual loss was longer in patient who was not treated.